Combining Positive and Negative Dichroic Fluorophores for Advanced Light Management in Luminescent Solar Concentrators. Issue 7 (3rd May 2014) - Debije, Michael G.; Menelaou, Christopher; Herz, Laura M.; Schenning, Albertus P. H. J.
<x xml:space="preserve">Abstract</x> This work describes the unexpected alignment of a common perylene bisimide fluorescent dye (Lumogen Red305) in a host liquid crystal matrix. The negative dichroic fluorophore orients with the primary absorption/emission dipole, corresponding to the physical long axis of the perylene bisimide core, perpendicular to the director of a host liquid crystal. A second absorption dipole, which lies perpendicular to the primary dipole and corresponding to the physical short axis of the perylene core, lies parallel to the host liquid crystal. Individual illumination of the two absorbing optical transition dipole moments of the Red305 dye results in a single linearly polarized emission. When Red305 is combined with a second positive dichroic Coumarin‐type fluorophore that aligns in the conventional manner in a liquid crystal host, that is, with an absorption dipole along the physical long axis of the fluorophore and the director of the host liquid crystal, advanced light management is possible, such as electrically switchable colors and directing emission light to different edges in a luminescent solar concentrator device.